Reclaiming the White Spaces: Spectrum Efficient Coexistence with Primary Users - Nychis, George; Chandra, Ranveer; Moscibroda, Thomas; Tashev, Ivan; Steenkiste, Peter (CoNext 2011: 7th ACM International Conference on Emerging Networking Experiments and Technologies, Tokyo, Japan, 2011)
TV white spaces offer an exciting opportunity for increasing spectrum availability, but white space devices (WSDs) cannot interfere with primary users, including TV channels and wireless microphones (mics). Mics are particularly challenging because their use is dynamic and it is hard to avoid interference since mic receivers are receive-only devices. For this reason the FCC and other regulatory agencies have made very conservatives rules that require WSDs to vacate any TV channel that is used by a mic. However, our measurements show that mics typically require only 5% of a channel, wasting as much as 95% of the spectrum. We present SEISMIC, a systems that enables WSDs and mics to operate on the same TV channel with zero audible mic interference. SEISMIC implements a MicProtector to measure the interference at the mic receiver and a signaling protocol to notify the WSD of impending interference. This allows the WSD to optimize its transmission (e.g. through subcarrier suppression) without impacting mics. We motivate and describe SEISMIC and present a detailed performance analysis that shows that SEISMIC can regain up to 95% of the spectrum in single mic scenarios, and up to 85% in many (10+) mic environments.
Selected as one of top 3 papers.